LEAF ANATOMICAL CHARACTERS OF SEVERAL TRUE MANGROVE SPECIES - Tihurua, Eka Fatmawati; Rahmawati, Kusuma; Agustiani, Esthi Liani; Ardhiyani , Marlina; Hutabarat, Prima W.K.; Nasution, Taufikurrahman; Sutikno, Sutikno; Surya, Dede; Damayanto, I Putu Gede P.; Apandi , Ismail; Dalimunthe, Syadwina H.; Martiansyah, Irfan; Junaedi, Decky Indrawan (Berita Biologi, 2023)
Anatomical characters of mangrove species have two important roles in mangrove studies that are as taxonomic supporting character and adaptation trait as a response to saline environment. Corks warts and sclereid are independent to environment, therefore those characters may be of taxonomic support. Mangrove species anatomical adaptation showed similar feature to drought stress or sclerophyll. The aim of this study is to distinguish anatomical characters of mangrove species that is taxonomical from habitat adaptation related anatomical characters. Fifteen true mangrove species from Banggai Kepulauan, Central Sulawesi and Banyuasin, South Sumatra were used to conduct this study. Paraffin method was used for leaf transversal section, while simple peeling using nitric acid was applied for epidermal section. The results showed that stomata distribution, cork warts, sclereid, and presence of water storage type were potential anatomical features for species identification. In addition, stomata type and epidermal cell walls also have the same potential but are still doubtful, therefore it will need to be studied further to ensure the useful of those characters. The use of anatomical characters for mangrove species identification, especially when they are in the vegetative stage, can quickly determine taxa at certain level. Those potential characters are such as glandular and non-glandular trichomes on the leaf surface.